Lesson In Islamic Jurisprudence - Muhammad Baqir As-Sadr (Brijbasi Art Press, 2007)
Used widely by shi're siminaries and value by sunni scholars for its intellectual rigor, muhammad baqir as-sadr lessons is key study of islamic jurisprudence.